1993
DOI: 10.1080/03079459308418948
|View full text |Cite
|
Sign up to set email alerts
|

A comparison and evaluation of techniques for diagnosis of avian tuberculosis in wildfowl

Abstract: SUMMARYTo control the epizootic of avian tuberculosis within the collections of captive wildfowl of The Wildfowl and Wetlands Trust an efficacious vaccine and a reliable diagnostic test are required.A number of potential diagnostic tests were compared for sensitivity and specificity using a flock of 178 feral barnacle geese (Branta leucopsis) at The Wildfowl and Wetland Trust's centre at Slimbridge, Gloucestershire. Evaluations were made of: serodiagnosis by an enzyme-linked immunosorbent assay (ELISA); agglut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 17 publications
0
6
0
1
Order By: Relevance
“…domesticus). Cromie et al (1993) observed cross-relativities between a polyclonal antiduck antibody and serum of feral Barnacle geese (Branta leucopsis). Baghian et al (1999) reported a broad crossreactivity of an anti-cockatiel IgY hyperimmune serum in the agar gel precipitation test, including several birds of the Order Psittaciformes.…”
Section: Discussionmentioning
confidence: 99%
“…domesticus). Cromie et al (1993) observed cross-relativities between a polyclonal antiduck antibody and serum of feral Barnacle geese (Branta leucopsis). Baghian et al (1999) reported a broad crossreactivity of an anti-cockatiel IgY hyperimmune serum in the agar gel precipitation test, including several birds of the Order Psittaciformes.…”
Section: Discussionmentioning
confidence: 99%
“…Karlson et al (1950) attempted to improve this rapid agglutination test by using a drop of whole blood added to a drop of antigen on a white tile, and later Rozanska (1965) created a staining technique allowing better visualization of fine agglutination. Rapid agglutination has been used with varying levels of success in poultry, geese, ducks, pheasants, as well as raptors and cranes (Moses et al, 1943;Karlson et al, 1950;Hiller et al, 1967;Rozanska, 1967;Kwatra 1972;Hawkey et al, 1990;Cromie et al, 1993). It was later demonstrated by Pavlas et al (1993) that, while fast and convenient, rapid agglutination tests are not always highly sensitive and often…”
Section: _________mentioning
confidence: 99%
“…They are easy to standardize and they are relatively fast and simple to use. Cromie et al (1993) investigated an ELISA and found it useful for screening some species of wildfowl for mycobacterial infection. In a later study the same group (Cromie et al, 2000) reported using an ELISA to evaluate humoral immune responsiveness after vaccination with mycobacterial antigens in several species of ducks, and reported that antibody responses were useful for evaluating exposure.…”
Section: _________mentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence that the water flowing through the captive wildfowl pens is the source of infection comes from isolation of M. avium from ‘soil, mud or muddy water’ at WWT Slimbridge (Schaefer et al , 1973), an epidemiological study of disease spread progressively downstream from the initial case of infection (Cromie, 1991) and studies showing that the pathology of affected birds indicates oral infection (Brown & Cromie, 1996). Attempts have been made to control ATB in WWT collections using a range of approaches including development of diagnostic tests (Cromie et al , 1993), vaccination (Cromie et al , 2000), management of the bird collection (Thorpe, 2000) including rotation according to age (R.L. Cromie, unpublished data) and through environmental control (Evans, 2001).…”
Section: Introductionmentioning
confidence: 99%